Personal goals as predictors of intended classroom goals: Comparing elementary and secondary school pre‐service teachers. (14th March 2012) - Daniels, Lia M.; Frenzel, Anne C.; Stupnisky, Robert H.; Stewart, Tara L.; Perry, Raymond P.
<x xml:space="preserve">Abstract</x> Background and Aims. The literature documents fewer classroom mastery goal structures in secondary school compared to elementary. However, little is known about how personal achievement goals may influence classroom goal structures. This is especially true at the level of pre‐service teachers. Our objective was to investigate if pre‐service teachers' personal goals predicted their intended classroom goal structures. Sample. Participants were 125 elementary and 175 secondary school pre‐service teachers from two Western Canadian universities. Method. Structural equation modelling was used to examine if the structural relationships and latent means of personal and intended classroom goal structures differed for elementary and secondary school pre‐service teachers. Results. The results revealed that personal goals predicted the goal structures that pre‐service teachers intended to establish; however, the relationships and means differed between elementary and secondary school pre‐service teachers. Specifically, personal mastery‐approach goals positively predicted classroom mastery goals much more strongly at the elementary than the secondary level. Furthermore, elementary pre‐service teachers had significantly higher latent mean scores on personal mastery‐approach goals than their secondary counterparts. Conclusions. It seems possible that the currently documented differences between classroom goal structures noted for elementary compared to secondary school may be based on the personal goals endorsed as pre‐service teachers. The results are further discussed in terms of alignment with research on practising teachers' personal and classroom goals and implications for teacher education.